PAG outreach programme at SMK Jeram: health education beyond the classroom - Mohd Mohtar, Nur Faezza; Omar, Noorkardiffa Syawalina; Ahmad, Zatul Akmar; Wan Nordin, Nadzratulaiman; Mat Jin, Norazilah (Faculty of Medicine, 2025)
On 18 June 2025, the Paediatric Adolescent Gynaecology (PAG) team from the Department of Obstetrics and Gynaecology (O&G), HASA UiTM, was invited to collaborate on the “Kasih NR @ Anti-Gangguan Seksual” programme at SMK Jeram, Kuala Selangor. The event was mainly organized by the Non-Resident UiTM, specifically targeting Form 2 to Form 5 students, and focused on raising awareness about sexual harassment and reproductive health. The main objective of the programme was to educate students on the critical issues of sexual harassment and abuse, while enhancing their knowledge and awareness of reproductive health, particularly menstrual health.